Whole blood-based in vitro culture reveals diminished secretion of pro-inflammatory cytokines and chemokines in visceral leishmaniasis. (September 2021) - Tasew, Geremew; Gadisa, Endalamaw; Abera, Adugna; Chanyalew, Menberework; Abebe, Markos; Howe, Rawleigh; Ritter, Uwe; Aseffa, Abraham; Laskay, Tamás
Abstract: The likelihood of being bitten by sand flies infected with Leishmania (L.) donovani is considered to be high for all inhabitants living in the endemic areas, but only a small ratio of the population develop symptomatic visceral leishmanisis (VL). Since adequate activation of antimicrobial immune response plays a key role in control of pathogens early after infection we hypothesized that a dysfunction of essential cells of the immune system is associated with disease development after infection with L. donovani . In order to obtain insights into the capacity of leukocytes to respond to L. donovani, a whole blood based assay was applied to evaluate the production of cytokines and chemokines in clinical VL versus Ethiopian endemic healthy control (EHC). In response to L. donovani, VL blood cultures showed significantly lower secretion of IL-12p70, IL-6, IL-17, IL-8 and IP-10 compared to EHC. On the contrary, there was a significantly higher secretion of IL-10 observed in VL compared to EHC. In response to LPS also a lower IL-1β, IL-12p70 and IL-6 secretion was observed in VL as compared to EHC. The data clearly indicate a diminished ability of blood leukocytes in VL to respond to L. donovani and to the TLR ligand LPS. This compromised response in VL may contribute to the severe disease development and enhanced susceptibility to secondary infections in VL.